Relation of Aortic Valve Morphologic Characteristics to Aortic Valve Insufficiency and Residual Stenosis in Children With Congenital Aortic Stenosis Undergoing Balloon Valvuloplasty - Petit, Christopher J.; Gao, Kevin; Goldstein, Bryan H.; Lang, Sean M.; Gillespie, Scott E.; Kim, Sung-In H.; Sachdeva, Ritu (The American journal of cardiology, 2016)
Aortic valve morphology has been invoked as intrinsic to outcomes of balloon aortic valvuloplasty (BAV) for congenital aortic valve stenosis. We sought to use aortic valve morphologic features to discriminate between valves that respond favorably or unfavorably to BAV, using aortic insufficiency (AI) as the primary outcome. All patients who underwent BAV at 2 large-volume pediatric centers from 2007 to 2014 were reviewed. Morphologic features assessed on pre-BAV echo included valve pattern (unicuspid, functional bicuspid, and true bicuspid), leaflet fusion length, leaflet excursion angle, and aortic valve opening area and on post-BAV echo included leaflet versus commissural tear. Primary end point was increase in AI (AI+) of ≥2°. Eighty-nine patients (median age 0.2 years) were included in the study (39 unicuspid, 41 functional bicuspid, and 9 true bicuspid valves). Unicuspid valves had a lower opening area (p <0.01) and greater fusion length (p = 0.01) compared with functional and true bicuspid valves. Valve gradient pre-BAV and post-BAV were not different among valve patterns. Of the 16 patients (18%) with AI+, 14 had leaflet tears (odds ratio 13.9, 3.8 to 50). True bicuspid valves had the highest rate (33%) of AI+. On multivariate analysis, leaflet tears were associated with AI+, with larger opening area pre-BAV and lower fusion length pre-BAV. AI+ was associated with larger pre-BAV opening area. Gradient relief was associated with reduced angle of excursion. Valve morphology influences outcomes after BAV. Valves with lesser fusion and larger valve openings have higher rates of leaflet tears which in turn are associated with AI.